EGFR基因少见突变型非小细胞肺癌的临床特征及应用EGFR-TKIs治疗效果评价 (Zhongguo Fei Ai Za Zhi, 2019)
BACKGROUND AND OBJECTIVE: Adenocarcinoma is the most common type of lung cancer. It has been clinically evaluated that therapiestargeting against the epidermal growth factor receptor (EGFR) as the clinical standard first-line treatment. The response and outcome of EGFR-tyrosine kinase inhibitors (TKIs) in patients harboring common mutations in EGFR kinase domain (deletion in exon19 and L858R in exon 21) has been well demonstrated, but not in rare or complex mutations. METHODS: A total of 150 patients that harbored rare or complex mutations in EGFR diagnosed by histopathology were included in this retrospective study. The clinical-pathological characteristics of all 150 patients as well as the response and progression-free survival (PFS) in 48 patients that received EGFR-TKIs in first/second/third line treatments weredescribed and analyzed. RESULTS: Patients were divided into four groups based on the mutation types: single G719X point mutation in exon 18 (n=46, 30.7%), single L861Q point mutation in exon 21 (n=45, 30.0%), other single rare mutation (n=14, 9.3%) and complex mutations (n=45, 30.0%). The result indicated thatthere was no correlation of EGFR mutation typeswith other parameters such as gender, age, clinical stage, pathology and smoking history. For the 48 patients that received EGFR-TKIs treatment, there were no significant differencesamong 4 groups in terms of objective response rate (ORR) and disease control rate (DCR) (54.5% vs 30.0% vs 0.0% vs 35.7%, χ(2)=3.200, P=0.34; 90.9% vs 85.0% vs 66.7% vs 92.9%, χ(2)=2.162, P=0.59). The median progress-free survival (mPFS) was 11.0 months (95%CI: 4.4-17.6), and in each group of different EGFR mutation types are 15.8 months (95%CI: 9.5-22.2), 8.0 months (95%CI: 5.1-11.0), 4.9 months (95%CI: 1.4-8.4) and 23.1 months (95%CI: 15.8-30.4)(χ(2)=7.876, P=0.049). CONCLUSION: The efficiency of targeting EGFR-TKIs on different types of rare or complex mutations was heterogeneous. The PFS may be better in patients that harbored complex mutations than those with single rare mutations. Further studies with larger sample size are necessary. Moreover, to discover novel therapeutic targets and develop new drugs are imminentfor those patientswith no response to the existing treatments.